EXCHANGE RATE DYNAMICS AND AGRICULTURAL SECTOR PERFORMANCE IN NIGERIA: AN ARDL APPROACH - AMAEGBERI, MICHAEL AYIBANUA; OKON, ASIDOK NSIKHE; ADIE, ADIE JOSEPH (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
The study investigates the responsiveness of the agricultural real sector to dynamics in exchange rate in Nigeria from 1986-2019. Data used for the study were sourced from Central Bank of Nigeria Statistical Bulletin and World Bank Indicator, (2019). The study adopts Augmented Dicky Fuller and Phillips Peron (PP) to test for unit root and where the result of the unit root was not clear, the co-integration test was conducted, findings revealed that only the variables in the impact model showed existence of long run relationship. The study revealed that some variables were stationary at level while some became stationary after first difference. The Auto Regressive Distributed Lag model was used to estimate the impact of exchange rate dynamics on Agricultural output performance in Nigeria. Findings revealed that exchange rate exerts negative impact on crop production in Nigeria only in the short run. Total rainfall, bank loan to agricultural sector, consumer price impact significantly on agricultural output in the long run but in the short run, only total rainfall and consumer price index exert significant impact on agricultural output in Nigeria. The study recommends that Central Bank of Nigeria should adopt managed exchange rate such that exchange rate does not exceed required threshold to ease flow of goods and services in the economy. The Central Bank of Nigeria should design stringent policies to increase commercial bank loans to agricultural sector in order to curb the adverse consequences of the exchange rate volatility on crop and fishery output in Nigeria.